Liver Ischemia and Reperfusion Induce Periportal Expression of Necroptosis Executor pMLKL Which Is Associated With Early Allograft Dysfunction After Transplantation - Shi, Shaojun; Bonaccorsi-Riani, Eliano; Schurink, Ivo; van den Bosch, Thierry; Doukas, Michael; Lila, Karishma A.; Roest, Henk P.; Xhema, Daela; Gianello, Pierre; de Jonge, Jeroen; Verstegen, Monique M. A.; van der Laan, Luc J. W. (Frontiers in Immunology, 2022)
Background: Early allograft dysfunction(EAD) following liver transplantation(LT) remains a major threat to the survival of liver grafts and recipients. In animal models, it is shown that hepatic ischemia-reperfusion injury(IRI) triggers phosphorylation of Mixed Lineage Kinase domain-like protein(pMLKL) inducing necroptotic cell death. However, the clinical implication of pMLKL-mediated cell death in human hepatic IRI remains largely unexplored. In this study, we aimed to investigate the expression of pMLKL in human liver grafts and its association with EAD after LT. Methods: The expression of pMLKL was determined by immunohistochemistry in liver biopsies obtained from both human and rat LT. Human liver biopsies were obtained at the end of preservation(T0) and ~1 hour after reperfusion(T1). The positivity of pMLKL was quantified electronically and compared in rat and human livers and post-LT outcomes. Multiplex immunofluorescence staining was performed to characterize the pMLKL-expressing cells. Results: In the rat LT model, significant pMLKL expression was observed in livers after IRI as compared to livers of sham-operation animals.Similarly, the pMLKL score was highest after IRI in human liver grafts(in T1 biopsies). Both in rats and humans, the pMLKL expression is mostly observed in the portal triads. In grafts who developed EAD after LT(n=24), the pMLKL score at T1 was significantly higher as compared to non-EAD grafts(n=40). ROC curve revealed a high predictive value of pMLKL score at T1(AUC 0.70) and the ratio of pMLKL score at T1 and T0(pMLKL-index, AUC 0.82) for EAD. Liver grafts with a high pMLKL index(>1.64) had significantly higher levels of serum ALT, AST, and LDH 24 hours after LT compared to grafts with a low pMLKL index. Multivariate logistical regression analysis identified the pMLKL-index(Odds ratio=1.3, 95% CI 1.1-1.7) as a predictor of EAD development. Immunohistochemistry on serial sections and multiplex staining identified the periportal pMLKL-positive cells as portal fibroblasts, fibrocytes, and a minority of cholangiocytes. Conclusion: Periportal pMLKL expression increased significantly after IRI in both rat and human LT. The histological score of pMLKL is predictive of post-transplant EAD and is associated with early liver injury after LT. Periportal non-parenchymal cells(i.e. fibroblasts) appear most susceptible to pMLKL-mediated cell death during hepatic IRI.